2022
DOI: 10.3390/vaccines10020152
|View full text |Cite
|
Sign up to set email alerts
|

Orally Administrated Recombinant Vaccinia Virus Displaying ROP4 Induces Protection against Toxoplasma gondii Challenge Infection

Abstract: Recombinant vaccinia viruses (rVVs) are attenuated viruses and are widely utilized as vectored vaccine platforms against numerous diseases. However, the protective efficacy of these rVV vaccines against Toxoplasma gondii and the resulting mucosal immunity has not been thoroughly assessed. Here, rVVs expressing the rhoptry protein 4 (ROP4) of T. gondii were generated. To evaluate the protection induced by the vaccines, mice were orally immunized with the ROP4-rVVs and subsequently challenge-infected with a leth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The roles of ROP4 include the regulation of host cell invasion, parasitic proliferation, and parasitic virulence regulation [ 24 ]. At present, research on ROP4 has mainly focused on various vaccines, including oral recombinant vaccines [ 25 ], virus-like particle (VLP) vaccines [ 26 ], recombinant baculovirus vaccines [ 27 ], and others. Research has shown that compared to a combination of two vaccines (ROP4VLP + ROP13VLP), the single ROP (4 + 13) VLP vaccine better promoted the expression of IgG, IgG1, IgG2a, and IgA in mouse serum.…”
Section: Role Of the Rop Of T Gondii In Crossing T...mentioning
confidence: 99%
See 1 more Smart Citation
“…The roles of ROP4 include the regulation of host cell invasion, parasitic proliferation, and parasitic virulence regulation [ 24 ]. At present, research on ROP4 has mainly focused on various vaccines, including oral recombinant vaccines [ 25 ], virus-like particle (VLP) vaccines [ 26 ], recombinant baculovirus vaccines [ 27 ], and others. Research has shown that compared to a combination of two vaccines (ROP4VLP + ROP13VLP), the single ROP (4 + 13) VLP vaccine better promoted the expression of IgG, IgG1, IgG2a, and IgA in mouse serum.…”
Section: Role Of the Rop Of T Gondii In Crossing T...mentioning
confidence: 99%
“… ROP39 ROP39 mediates an IRGB10-specific parasitic effect and regulates acute Toxoplasma virulence [ 24 ]. ROP54 ROP54 has been recommended as a vaccine candidate for toxoplasmosis [ 25 ]. ROP54 modulates T. gondii virulence and host GBP2 loading [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Vaccination is one of the most significant achievements for controlling and preventing infectious diseases; it is also an ideal strategy for toxoplasmosis [ 6 , 7 ]. Current studies on the T. gondii vaccine mainly focused on killed vaccines, live attenuated vaccines [ 8 ], specific component vaccines [ 9 , 10 ], subunit vaccines [ 11 ] and nucleic acid vaccines [ 12 ]. Immunoprotection is still an important challenge for the T. gondii vaccine.…”
Section: Introductionmentioning
confidence: 99%